Probabilities of reaching required diffusion of granular energy technologies in European countries - Nik Zielonka; Evelina Trutnevyte (iScience)
Summary: To support discussions around the feasibility of the energy transition, we present probabilistic projections of the expected baseline diffusion of solar photovoltaics, wind power, biogases, heat pumps, and low-carbon passenger vehicles in 39 European countries for 2023–2050 under current contextual conditions. We then compare the projected capacities against those required for reaching net-zero greenhouse gas emissions by 2050. We create our projections using 72 different variants of diffusion models that we validate using hindcasting (2012–2022) and weight according to their performance. We find a notable expected growth in solar photovoltaics, heat pumps, and battery electric vehicles in the majority of European countries. However, most countries are unlikely to reach the required capacities for net-zero emissions of wind power and biogases with high confidence, and battery electric vehicles with lower confidence. Probabilities and confidence levels of reaching required capacities of solar photovoltaics and heat pumps vary the most between countries.